THE IMPACT OBESITY HAS ON EARLY PERINATAL OUTCOMES AND NEONATAL MORBIDITIES IN PREMATURE INFANTS - Sliusarieva, A.V.; Kovalova, O.M.; Pokhylko, V.I. (World of Medicine and Biology, 2022)
In an epidemiological retrospective study, which included 4.874 women, the frequency of obesity of various degrees among pregnant women, increased risks of adverse pregnancy complications and obstetric outcomes, in particular hypertension disorders, preeclampsia, uterine inertia, use of emergency cesarean section, excessive fetal growth. At the same time among women with stage ІІІ obesity compared to women of the stage І, the risks of having hypertensive conditions are 3.5 times higher, the uterine inertia is twice as high, preeclampsia is 56.8 % and excessive fetal growth is 21.3 %. It has been shown that there is no impact of obesity on the premature birth of babies. Large-for-gestational-age babies born prematurely to obese (non-diabetic) mothers have been shown to have an increased risk of jaundice (RR 3.08) and neonatal hypoglycemia (RR 9.11) and no such risk compared with those of normal weight regarding the occurrence of other diseases (intraventricular hemorrhages, birth asphyxia, respiratory distress, hemodynamic significance patent ductus arteriosus, retinopathy). No significant differences were noted between the children of both groups in the frequency of noninvasive/invasive ventilatory support, oxygen support, and parenteral nutrition.
Keywords: pregnant; maternal obesity; perinatal outcomes; premature; large for gestational age; morbidity